Optimalisasi Pendayagunaan Mediasi Sebagai Alternatif Penyelesaian Sengketa Merek - Aryani, Fajar Dian; Pratama, Erwin Aditya; Indriasari, Evy (Universitas Pancasakti Tegal, 2021)
Various forms of administrative legislation and/or economic administration laws that